1995
DOI: 10.1007/bf02306627
|View full text |Cite
|
Sign up to set email alerts
|

Mass traumatic terror in Oklahoma City and the phases of adaptational coping, part I: Possible effects of intentional injury/harm on victims' post-traumatic responses

Abstract: The bombing in Oklahoma City

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Clinical experience has shown that the pervasive impairments in biological, psychological, and social areas of functioning in violence-traumatized individuals require an intervention strategy which integrates multiple schools of therapy and pharmacotherapy (Crump, 1984;Parson, 1984Parson, , 1994aParson, , 1995bParson, , 1995c. Additionally, the pervasive effects of trauma in children exposed to violence tend to require a conceptualization that is beyond single-theory techniques--one that employs, for example, behavior therapy, cognitive therapy, and other therapies.…”
Section: Systems Of Therapy: Psychotherapy Integration In Child Traummentioning
confidence: 96%
See 2 more Smart Citations
“…Clinical experience has shown that the pervasive impairments in biological, psychological, and social areas of functioning in violence-traumatized individuals require an intervention strategy which integrates multiple schools of therapy and pharmacotherapy (Crump, 1984;Parson, 1984Parson, , 1994aParson, , 1995bParson, , 1995c. Additionally, the pervasive effects of trauma in children exposed to violence tend to require a conceptualization that is beyond single-theory techniques--one that employs, for example, behavior therapy, cognitive therapy, and other therapies.…”
Section: Systems Of Therapy: Psychotherapy Integration In Child Traummentioning
confidence: 96%
“…Studies on the effects of violence on children's lives have focused on effects of violence on children's functioning and well-being (Parson, 1995a;Pynoos et al, 1987), on families (Gelles & Conte, 1990;, on society (Surgeon General's Workshop on Violence and Public Health, 1991), on prevention considerations (Bell, 1992;Prothrow-Stith, 1991) and intervention strategies (Parson, 1995b(Parson, , 1995cPynoos & Nader, 1988), on neighborhood infrastructures, as well as on the economic impact, and needed legislative initiatives ('A Vision for America 's Future," 1989).…”
Section: Inner City Children and Lethal Community Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have thus shown that dissociative symptoms present at the time of combat trauma were better predictors for post-traumatic pathology, even better than the intensity variable (shown as the best predictor of current trauma psychopathology in previous studies). Dissociative symptoms have been found in child and pediatric victims of abusive violence and neglect (Parson, 1995c(Parson, , 1997aPutnam & Guroff, 1986;of Suhr, 1986), of disasters (Cardena & Spiegel, 1993;Lindy & Titchener, 1983;Parson, 1995aParson, , 1995cSanders & Giolas, 1991), of burn injury, of physical and sexual violence (Parson, 1996c;Perry et al, 1992), and in combat veterans (Bremner & Brett, 1997;Parson, 1984).…”
Section: "The Body Keeps the Score": Somatopsychic Conditioned Responsementioning
confidence: 99%